Preventive effects of Moringa oleifera on obesity and hyperlipidaemia : a systematic review - Sivanesan Raja Kumar; Norliza Muhammad; Mary Nancy Fernandez; Nur Azlina Mohd Fahami (Penerbit Universiti Kebangsaan Malaysia, 2022)
Obesity and hyperlipidaemia are metabolic dysregulations, arising from poor lifestyle and excessive dietary intakes which may contribute to many chronic diseases if not treated. Studies have shown that plant-based supplementations can suppress this metabolic dysregulation. Moringa oleifera (MO) is a plant that is known to be nutritious and can alleviate obesity and hyperlipidaemia owing to its medicinal properties. A literature search on the effects of MO on obesity and hyperlipidaemia using electronic databases which included Ovid Medline and Scopus was performed. Specific descriptors were used to perform the search strategy. The articles were selected based on the principles that report on the effects of MO on obesity and hyperlipidaemia. Titles of the articles were screened for Moringa oleifera OR obesity OR hyperlipidaemia. Twenty-nine articles, 19 from Ovid Medline and 10 from Scopus were selected based on the inclusion and exclusion criteria. A flow chart was created to represent the study selection. Based on the chosen articles, MO was shown to suppress obesity and hyperlipidaemia directly and indirectly through the regulation of gene expression, enzyme activity and adipocytokines. Through animal trials, MO demonstrated promising results in alleviating obesity and hyperlipidaemia. More human trials should be performed to strengthen the accomplished effects seen on animals. As there were no side effects identified in animal studies, it could be recommended to patients with obesity and hyperlipidaemia.